Photocatalytic properties, mechanical strength and durability of TiO2/cement composites prepared by a spraying method for removal of organic pollutants. (September 2020) - Feng, Shenglei; Song, Junwei; Liu, Fanghua; Fu, Xiang; Guo, Hui; Zhu, Jielu; Zeng, Qingli; Peng, Xiaoying; Wang, Xinfei; Ouyang, Yong; Li, Fei
Abstract: TiO2 /cement composites were prepared by a spraying method to degrade organic pollutants. After coated with waterproof liquid, pure cement pastes/mortars were sprayed with TiO2 suspensions with different TiO2 contents and spraying times. Photocatalytic properties, mechanical strength and durability were studied. Maximum photocatalytic activity and uniform TiO2 distribution were achieved at the optimal conditions of 10 wt% TiO2 content in suspension and 3 spraying times. The TiO2 /cement pastes had better degradation performance over Rhodamine B (RhB) and methylene blue (MB) than that over methyl orange (MO). After 20 times of cycling degradation, the photocatalytic efficiencies had no significant reduction. The TiO2 /cement mortars had good mechanical strengths, meeting the mechanical demands of wastewater treatment tanks. In durability, the TiO2 /cement mortars had better water penetration resistance, chloride penetration resistance and anti-carbonation than pure cement mortars. Highlights: TiO2 -cement paste/mortar was prepared by a spraying method. Photocatalytic tests included dye category, acidic/basic soaking and circulation. Mechanical strength and durability were researched. After circulation, TiO2 -cement paste still had higher degradation efficiency.